Stardust - Gaiman, Neil. (New York : HarperTeen, 2009)
Young Tristran Thorn, having lost his heart to the lovely but cold Victoria Forester, leaves the safe English town of Wall and sets out into a strange world on a quest to retrieve a fallen star he has promised to his beloved.
Young Adult
Young Adult
Keywords: Man-woman relationships -- Fiction; Meteors -- Fiction; Adventure fiction; Love stories; Man-woman relationship -- Fiction; Meteors -- Fiction; Fantastic fiction; Fantastic fiction; Adventure fiction; Love stories